Effectiveness and Efficiency of Periodic Motor Vehicle Testing Through the Quality of Public Services on the Satisfaction of Service Users - Pribadi, Punkky Januar; Indrawan, Rully; Gunawan, Aang (Dinasti Publisher, 2025)
This study aims to analyze the effectiveness and efficiency of periodic motor vehicle testing through the quality of public services and its impact on user satisfaction at the Cilincing Motor Vehicle Testing Unit (UPPKB). A quantitative survey design was employed, involving 95 service users selected through purposive sampling. Data were collected using a questionnaire measuring service quality (tangibles, reliability, responsiveness, assurance, and empathy), effectiveness, efficiency, and user satisfaction. Multiple linear regression analysis was used to examine the relationships between variables. The findings indicate that public service quality significantly influences user satisfaction, with responsiveness and assurance as the dominant factors. Effectiveness is reflected in the accuracy of testing procedures and results, while efficiency is evident in optimizing time and cost. However, challenges such as long queues and inadequate supporting facilities need improvement. This study recommends enhancing infrastructure, training staff, and implementing digital systems to improve service quality and user satisfaction at UPPKB Cilincing. The study results show that effectiveness and efficiency positively and significantly impact service quality and user satisfaction. Effectiveness, which is reflected in the smoothness, timeliness, and minimal obstacles in the testing process, has been proven to increase satisfaction and service quality. Similarly, efficiency through optimal resource management can accelerate services, reduce waiting times, and strengthen the public's positive perception of the quality of public services